Laporan Tugas Akhir Pada Kantor Notaris dan PPAT Nurhadi Darussalam, S.H., M.Hum PROSEDUR PENDAFTARAN HIBAH MELALUI PEMBERIAN KUASA PADA KANTOR PERTANAHAN KABUPATEN SLEMAN - , INTAN PERWITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The tittle of this final report is âADMISSION PRODUCE GRANT THROUGH THE POWER OF GIVING LAND DISTRICT IN SLEMAN REGENCYâ be writer because the author would like to better understand the notion of grants and grant application procedures through provision of power in SlemanRegency Land Office so I can apply in life in the surrounding communities who need assistance on a grant or grant application procedures with an authentic deed. The purpose of this final project is to meet the graduation requirements of the Diploma 3Program Vocational School of Law, University of GadjahMada and to get a law degree Associate Expert (Amd). Benefit of Field Work Practice is to provide real experience of the authors in the application of the theory taught in college. The results of this final project is the definition of an action grant approval of the grantor at the time of his life, freely and irrevocably to submit something for the purpose of the object grantees. The registration is done with a power of attorney grants that are specific authentic. The process of obtaining a grant to the issuance of a certificate of registration by the Land Office grants Sleman Regency is 2 (two) to 3 (three) months from the time of registration.